Foreign expansion of small firms - Chen, Rongxin; Martin, Marc J (Journal of Business Venturing, 2001)
This research analyzes foreign expansions of small firms. In particular, we look at how a small firm's foreign expansion is affected by the join effects of prior foreign business involvement and other factors. We found that when encountering performance downturn and market size decline, small firms with prior foreign business involvement are more likely to use foreign expansion to deal with the problems. This suggests that organizational characteristics mediate the relationship between competitive threats and foreign expansion activities. We also found that small firms' foreign diversification is affected by their product and domestic expansions, suggesting foreign activities of small firms are closely related to their non-foreign strategies.